Uma análise vetorial de propagação UHF e de microondas em áreas urbanas e rurais usando Teoria do Traçado do Raio - Silva Júnior, Edgar (2007)
In this work we present propagation models for urban, suburban and rural areas. A vectorial analysis of the two-ray model for elevated aerials is presented as well as vectorial analyses of the (two-dimensional) 2D and (three-dimensional) 3D waveguide models. For all, an ideal dipole is assumed to be the transmitting aerial. The two-ray model describes rural areas, highways, and more desert suburban areas and it consists of a ray that arrives at the receptor along a straight line and of a ray that arrives at the receptor after a ground reflection. For this model parallel and perpendicular polarizations are investigated. Parallel polarization is specifically analyzed in two ways: with and without approximations. For the model analyzed without approximations, the field radiation pattern of the dipole and the vectorial analysis of the field are accounted. For the model analyzed with approximations only an algebraic sum is carried out. Comparisons between these two models are performed as well as an analysis of the error versus r distance. Still for the non-approximated two-ray model, comparisons between horizontal and vertical components of the electric field, comparisons between horizontal and vertical components themselves for several transmitter heights and comparisons with measurements, are provided. The 2D and 3D waveguides describe street cities. The 2D waveguide model, whose main feature is having the same transmitter and receptor aerial heights, consists of rays arriving at the receptor along a straight line, after a ground reflection and along multiple lateral reflections. This model is analyzed in two ways: with and without slits for horizontal and vertical polarizations and likewise the two-ray model a comparison between the approximated and non-approximated analyses is performed. Still for the 2D waveguide, a comparison between the total field and the field due to lateral reflections only is carried out. The 3D waveguide model, whose main feature is having different transmitter and receptor aerial heights, consists of rays arriving at the receptor along a straight line, after a ground reflection, along multiple lateral reflections and along wall-road (border-ground) reflections. This model is likewise analyzed in two ways: with and without slits for horizontal and vertical polarizations and a comparison between the total field and the field due to lateral reflections only is also carried out. In the slits analysis, two kinks of models are developed: one for periodical slits and another one that takes into account the street databases, which is loaded in the program from its respective data file. For all the 3D waveguide model stages calculated data are compared to measured data, ratifying the applicability of the model described. Comparisons provided with measured data show that a vectorial and field radiation pattern analysis can be a very useful tool toward increasing theoretical analysis in spite of empirical analysis in the field of prediction.